Ultrafast colorimetric humidity-sensitive polyelectrolyte coating for touchless control. Issue 1 (9th November 2016) - Yu, Li; Xu, Haolan; Monro, Tanya M.; Lancaster, David G.; Xie, Yi; Zeng, Hongbo; Chen, George Y.; Liu, Xiaokong
Abstract : A touchless control system that can be operated by a humidity signal is developed based on colorimetric humidity-sensitive materials. Abstract : Herein we report the visible colorimetric humidity-sensitive properties of the layer-by-layer assembled poly(diallyldimethylammonium) (PDDA)/poly(styrenesulfonate) (PSS) polyelectrolyte coatings and their application for a touchless control system that can be accessed by humidity change. The as-developed touchless control system enables humidity signals, such as those imparted by human breath or a close-proximity fingertip, to switch a light-emitting diode and trigger a computer to implement commands ( e.g., making phone calls and playing music). The PDDA/PSS coatings exhibit different colors at different thicknesses, which results from the interference of visible light in the coating. Notably, they can undergo vivid and reversible color changes that span the whole visible spectrum at an ultrafast speed ( ca. 35 ms) according to the local humidity change. Exploiting the ability of the coating to modulate light, the output optical signal ( i.e., color change) was converted into an electrical signal by irradiating the coating with a beam of monochromatic light and collecting the reflected modulated light using a photodetector. The obtained electrical signal was subsequently processed and used as an input signal for touchless control that is accessible by a humidity signal. The as-developed touchless control system is applicable for the touchless interface of electronic devices, smart switches, automotive, smart buildings, and so forth.